Environmental conditions and beekeeping practices associated with Nosema ceranae presence in Argentina - Pacini, Adriana Cecilia; Molineri, Ana Ines; Antúnez, Karina; Bulacio Cagnolo, Natalia Veronica; Merke, Julieta; Orellano, Emanuel; Bertozzi, Ezequiel; Zago, Luis Fernando Basili; Aignasse, Andrea Maria Elisa; Pietronave, Hernan Pablo; Rodriguez, Graciela Adriana; Palacio, María Alejandra; et al. (Springer, 2021)
A longitudinal study was carried out in order to evaluate Nosema spp. spore counts in two key moments of the year (late autumn and spring) in honeybee colonies from five eco-regions of Argentina. Three hundred and sixty colonies were randomly selected and the infestation level of Nosema spp. and Varroa destructor was assessed in autumn and spring of 2015. In addition, a questionnaire concerning all management practices applied in the colonies was answered by the beekeepers. Generalized linear mixed effect models were performed to determine the relationship between risk factors associated with Nosema spp. spore counts in each eco-region. Data were scanned to identify colonies cluster with a higher probability of achieving high values of Nosema spp. abundance for each sampling period. Spatial distribution of colonies with a higher risk of achieving high Nosema spp. abundance seems to be explained by geographical conditions associated to climatic conditions and some management practices implemented in each eco-region.